Pengembangan Flipbook IPA Dalam Bingkai Kearifan Lokal NTT Untuk Menunjang Pemahaman Konsep Siswa SMP - Claudia Mariska M Maing; Maria Ursula Jawa Mukin; Oktavianus Ama Ki`I (Postgraduate, University of Mataram, 2026)
The widespread availability of instructional materials, particularly textbook packages, allows students to access learning resources either independently or through schools. However, many of the images and phenomena presented in these materials originate from contexts unfamiliar to students, requiring them to imagine situations they have never encountered. To address this issue, instructional materials were developed based on real-world problems drawn from local contexts, specifically salt production and gula lempeng (traditional palm sugar) production from palm sap, to provide meaningful and contextual learning experiences. This study employed a research and development approach using the ADDIE model. Data collection involved questionnaire techniques for validating the instructional materials through expert validation sheets, as well as test techniques to measure students’ conceptual understanding after implementation. The validation results showed that the instructional materials achieved high feasibility scores in terms of material (0.90), language (0.85), presentation (0.83), and media (0.86), all of which fall within the very valid category. Furthermore, students’ conceptual understanding test results exceeded 80%, indicating very good mastery of the concepts. These findings suggest that science instructional materials based on local wisdom and supported by a flipbook format are highly valid and effective in optimizing students’ conceptual understanding of temperature, heat, and thermal expansion.